Consensus‐based good practice guidelines for clinical psychologists to support care staff in enabling sexual expression in people with intellectual disabilities—A Delphi study. Issue 2 (2nd October 2019) - English, Brad; Tickle, Anna; das Nair, Roshan; Moore, Kate
Abstract: Background: Care staff supporting people with intellectual disabilities (PWID) report accepting views on PWID's sexual expression, but people with intellectual disabilities report their sexual expression is restricted by care staff. Methods: We recruited a panel of 17 UK clinical psychologists experienced in helping care staff support PWID's sexual expression. We used the Delphi Method to develop consensus‐based practice guidelines for UK clinical psychologists supporting care staff in this way. Results: Having proposed three guidelines each in Round One, panel members reached consensus (≥90% agreement) that 12 were important, falling under four themes: "Addressing staff attitudes, " "Addressing uncertainty about rights and responsibilities of people with intellectual disabilities, " "Locating the problem, being part of the solution, " and "Supporting care staff to understand and reflect upon their role." Conclusions: Clinical psychologists help care staff support PWID's sexual expression by normalizing care staff concerns, encouraging reflection, clarifying PWID's rights, and prompting those at managerial and service level to support care staff.